Sistem Rekomendasi Kamera Mirrorless Dengan Metode Simple Multi Attribute Rating Technique (SMART) - Marvellino; Viny Christanti Mawardi; Manatap Dolok Lauro (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
Photography are an activity that can be done through a lot of other media, some uses DSLR (Digital Single Lens Reflex) camera, Mirrorless and even from their smartphones. Choosing a mirrorless camera by those who doesn’t have the knowledge of the specifications of a camera might be a problem by itself. The problem itself rose because there’re a lot of criterias that need to be considered in getting the right one and due to lack of information. That is why recommendation system based on website are developed which can help users choosing the right product using SMART (Simple Multi Attribute Rating Technique) method. SMART method are a method for taking decisions that are multi attribute used for supporting decisions which have other alternatives. In developing this website it uses 5 brands of camera that is Canon, Fujifilm, Nikon, Panasonic and Sony. The validity test based from UAT (User Acceptance Rate) of 35 respondents gives a result of 85.71% accuracy that agrees that the recommendation system is appropriate to what user wants and proves that the system gaves the recommendation based on what user wants and beneficial to be used.